UPAYA PENINGKATAN MOTIVASI MAHASISWA DALAM MATA KULIAH NIHONJIJO - Miranti Artarina (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The purpose of this study is to find innovations to increase the motivation of Japanese literature students at Universitas Nasional Pasim Bandung during Nihonjijo lectures. The object of this study is the learning resources used during the learning of the Nihonjijo lectures from 2015-2017. The method used is descriptive method. Data collection techniques are carried out through library studies and documentation studies referring to learning material in the Nihonjijo Lesson Plan. Observation techniques during lectures and interviews with students who contracted the Nihonjijo course in semester 2 were also carried out to obtain supporting data. The results obtained in this study are (1) students become more motivated when learning Nihonjijo by utilizing audio-visual learning resources, (2) students become more motivated to explore knowledge about Japanese culture and daily life by making presentations and discussions using Japanese, (3) the use of basic Japanese as the language of instruction during Nihonjijo lectures helps students to hone their language skills in Japanese in a good and acceptable way.